Pedagogy VS Stereotypes - V I Kazarenkov (Peoples' Friendship University of Russia (RUDN University), 2011)
A brief review of the International scientific conference "Pedagogy towards Stereotypes", taking place in University of Warmia and Mazury in Olsztyn (Poland) is submitted in the publication.